Vulnerability assessment tools for infectious threats and antimicrobial resistance: a scoping review protocol. Issue 11 (18th November 2019) - Jeleff, Maren; Lehner, Lisa; Giles-Vernick, Tamara; Dückers, Michel L.A.; Napier, A. David; Jirovsky, Elena; Kutalek, Ruth
Abstract : Introduction: This protocol will guide and explain the working process of a systematic scoping review on vulnerability assessment tools in the field of infectious disease outbreaks and antimicrobial resistance (AMR) crises. The scoping review will appraise existing tools or methodologies to identify local level vulnerabilities in the context of infectious disease outbreaks and AMR. Due to this focus on infectious threats and AMR, the review also considers articles using a 'One Health' approach to assess the vulnerability of individuals, groups and practices in human–animal–environment interactions. Given the broad nature of vulnerability, we aim to allocate studies discerning the process of identifying vulnerable or at-risk groups during a crisis, instead of studies taking vulnerability only as a starting point. Because considerable research has been conducted on vulnerability, disasters and climate change, we will also assemble tools developed from these fields. To our knowledge, this is the first planned systematic scoping review of vulnerability assessment tools for disease outbreaks and AMR, taking into account practices at the human–animal–environment interface that can lead to increased risk of exposure of individuals to infections, pathogen spillovers or epidemics. Methods and analysis: To develop the protocol, we used the Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols checklist (PRISMA-P 2015) in compliance with the PRISMA Extension for Scoping Reviews Explanation and Elaboration. With the assistance of an experienced research librarian, we developed the search strategy, which targeted the following databases: Medline, Global Health database, Web of Science and Embase. A second strategy was developed for Epistemonikos, African Journals Online and Global Index Medicus because these databases do not provide the infrastructure for an advanced search. We consider studies published between 1978 and 2019 and include articles, book chapters, websites and grey literature from selected non-governmental organisations and non-profit organisations working in the health field. We contact them directly regarding whether they are working with or have developed a vulnerability assessment tool. To address the dynamic nature of our investigation, we develop a flow diagram which we continually update to reflect the selection process. Two reviewers (MJ and LL) independently screen the literature and resolve conflicts through discussion rounds. Data extraction will be conducted by four researchers (MJ, LL, EJ and RK) through inductive and deductive coding. Extracted data will be systematically compared and divergences highlighted. Ethics and dissemination: Ethical approval is not required because this study does not involve collection of primary data. The purpose of this review is to disseminate a catalogue of vulnerability assessment tools and a brief summary of key results and recommendations for SoNAR-Global partners in Bangladesh, Ukraine and Uganda. The catalogue will be made publicly available. On the basis of our results, SoNAR-Global partners will pilot one of these tools.